Branding and Digital Marketing Innovation for Siwang MSMEs Empowerment in Indramayu West Java - Jaya, Fitra; Yati, Yati; Sucipto, Sucipto; Siswanto, Romi; Kadarisman, Kadarisman; Gayatria Oktalina; Widayanti, Agnisa (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to enhance the branding capacity and digital marketing competencies of “Siwang”, a traditional shrimp-paste-based MSME in Gantar Subdistrict, Indramayu Regency. The intervention employed a participatory approach, encompassing needs assessment, digital literacy training, content creation workshops, and mentorship in utilising social media and online marketplaces. Evaluation was conducted through questionnaires and participatory observation. Quantitative data were analysed using descriptive statistics to determine partner satisfaction and competency improvements, while qualitative insights were interpreted thematically to capture behavioural changes and contextual relevance. The results indicate a substantial improvement in branding awareness, social media management skills, and production efficiency, supported by the introduction of appropriate digital and production tools. Key evaluation indicators demonstrated achievement rates above 85%, with overall partner satisfaction exceeding 90%. This program not only strengthened the business competitiveness of the MSME but also laid a foundation for sustainable digital transformation rooted in local cultural values. The model is recommended for replication among similar rural enterprises with high artistic and economic potential.